PENGARUH PELATIHAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT.OSI ELECTRONICS BATAM - SIMANJUNTAK, AGUSTINA; Nainggolan, Nora (LPPM Universitas Putera Batam, 2022)
In the current era of globalization, Human Resources (HR) is one of the supporting factors to complete work and is a factor in the success of a company. This will be a problem for employees, especially in terms of experience and training status because it will have an impact on employee performance in the company. The purpose of this study was to determine the magnitude of the influence partially or simultaneously between training and work experience on employee performance. The technique used in this study is to identify the effect of partial (t test) and simultaneous (F test) between training variables (X ) and work experience (X ) on employee performance (Y) at PT. Osi Electronics batam. Data collection techniques on This research was conducted by distributing questionnaires to employees of PT. Osi Electronics Batam with 158 samples.The results of the coefficient of determination (R2) in the summary model which can be seen from the R Square of the training variable, work experience and employee performance are 0.676or 67.6% and while the t-test on the training variable (X ) has a arithmetic value of4.737and t table2.6079 where obtained t count > t table, and the significance value is 0.000 below 0.05 and the work experience variable (X ) where it is obtained that t count > t table, and the significance value is 0.000 below 0.05 Based on the results of the simultaneous test, Fcount is 161.410In this test, the correlation between training and work experience on employee performance was obtained. This statement is supported by a calculated F value greater than F table, and a significance value of 0.000 less than 0.05. This indicates that the variables of training and work experience stimulants have a significant effect on employee performance.